SEX HORMONES IN THE SALIVA AND PERIODONTAL HEALTH OF CHILDREN IN PUBERTY - Nadezhda Mitova; Maya Rashkova (Peytchinski Publishing, 2019)
Introduction: Children at the age of sexual maturation are suitable subjects for studying the influence of sex hormones on periodontal health, due to increased hormone levels as well as the increased frequency of gingival conditions at that age. Aim: To study the quantity of sex hormones in the saliva and the periodontal health of children in puberty. Material and methods: 60 children aged 10-14 years subjected to monitoring- 30 without gingivitis (up to 25% PBI) and good oral hygiene and 30 children with plaque-induced gingivitis (over 50% PBI). For the study of sex hormonesstradiol, progesterone and testosterone), samples of unstimulated saliva were taken fasting in the morning, which were tested by using marked immunological analysis and liquid chromatography with mass spectrometry (LC-MS (MS(QQQ)). Results: The results of this study show that from the ages of 10 to 14, there is no significant difference in the levels of the sex hormones in the saliva (P>0.05). In children with gingivitis in relation to healthy children, only estradiol exhibits plausibly higher values (P<0.05). Progesterone and testosterone show no variation based on periodontalatus (P>0.05). Conclusion: Saliva is an appropriate, non-invasive environment for studying the quantities of sex hormones and their link to oral pathology.